2023
DOI: 10.1002/adhm.202300012
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Triggered Nitric Oxide Nanogenerator with Highl‐Arginine Loading for Synergistic Photodynamic/Gas/Photothermal Therapy

Abstract: The development of nanomedicines that combine photothermal therapy (PTT) with photodynamic therapy (PDT) is considered promising for cancer treatment, but still faces the challenge of enhancing tumoricidal efficiency. Fortunately, apart from the well‐acknowledged effect on direct tumor cell‐killing, nitric oxide (NO) is also considered to be effective for the enhancement of both PTT and PDT. However, both the low loading efficiency of NO precursor and the short half‐life time and diffusion distance of NO hampe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…To demonstrate the excellent photothermal properties of FP-POP and iFP-POP, the laser-induced temperature change trends under 638 nm laser irradiation were finely examined by adjusting either the concentration of the polymers (25–400 μg mL –1 ) or the laser power density (0.5–2.0 W cm –2 ). As displayed in Figure a,b, both polymers showed concentration-dependent warming behaviors . After 15 min of laser irradiation (638 nm, 1.5 W cm –2 ), the temperatures of FP-POP and iFP-POP were gradually increased from 30.9 to 68.9 °C and from 32.4 to 74.2 °C, respectively, with a concentration variation from 25 to 400 μg mL –1 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…To demonstrate the excellent photothermal properties of FP-POP and iFP-POP, the laser-induced temperature change trends under 638 nm laser irradiation were finely examined by adjusting either the concentration of the polymers (25–400 μg mL –1 ) or the laser power density (0.5–2.0 W cm –2 ). As displayed in Figure a,b, both polymers showed concentration-dependent warming behaviors . After 15 min of laser irradiation (638 nm, 1.5 W cm –2 ), the temperatures of FP-POP and iFP-POP were gradually increased from 30.9 to 68.9 °C and from 32.4 to 74.2 °C, respectively, with a concentration variation from 25 to 400 μg mL –1 .…”
Section: Resultsmentioning
confidence: 89%
“…As displayed in Figure 3a,b, both polymers showed concentration-dependent warming behaviors. 46 After 15 min of laser irradiation (638 nm, 1.5 W cm −2 ), the temperatures of FP-POP and iFP-POP were gradually increased from 30.9 to 68.9 °C and from 32.4 to 74.2 °C, respectively, with a concentration variation from 25 to 400 μg mL −1 . Even at a low concentration of 200 μg mL −1 , the temperatures of FP-POP and iFP-POP also increased to 57 and 58.1 °C, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…In order to verify the biological safety of L-Si QDs and the phototoxicity of L-Si QDs to kill cancer cells, the dark toxicity of L-Si QDs to normal cells and phototoxicity to tumor cells were tested by MTT assay [68]. The MTT results of L-Si QDs on HU-EVC normal tissue cells in figure 6(a) showed that L-Si QDs had excellent biological safety.…”
Section: In Vitro Therapymentioning
confidence: 99%
“…The former could be used for gas therapy, and the latter provided CDT and could be used as a contrast agent for T1-weighted MRI . Similarly, NO enrichment leads to cellular DNA damage while enhancing PDT by inhibiting tumor cell respiration and oxygen consumption . Gox and l -arg have also been coadministered to produce NO for gas/starvation therapy of tumors by consuming glucose .…”
Section: Introductionmentioning
confidence: 99%